The autistic brain [compact disc, unabridged] : thinking across the spectrum - Grandin, Temple; Panek, Richard (Recorded Books, 2013)
"A cutting-edge account of the latest science of autism, from the best-selling author and advocate Temple Grandin is a star, a Time Magazine top 100 Hero and an inspiration to millions worldwide. Since she started writing and speaking about autism, the number of people diagnosed with it has skyrocketed--but so has the research that is transforming our understanding of the autistic brain. Now she brings her singular perspective to a thrilling journey through the autism revolution. Weaving her own experience with remarkable new discoveries, she introduces the neuroimaging advances and genetic research that link brain science to behavior, even sharing her own brain scans from numerous studies. We meet the scientists and self-advocates who are introducing innovative theories of what causes, how we diagnose, and how best to treat autism. She highlights long-ignored sensory problems and the treatments that might help them, and warns of the dangers of politics defining the diagnosis of autism spectrum. Most exciting, in the science that has begun to reveal the long-overlooked strengths conferred by autism, she finds a route to more effective mainstreaming and a way to unleash the unique advantages of autistic people. From the "aspies" in Silicon Valley to the five-year-old without language, Grandin understands the true meaning of the word spectrum. The Autistic Brain is essential reading from the most respected and beloved voices in the field"--